Case Report: Hypertension Accompanied by Obesity with Herbal Consumption of Soursop Leaf Boiling - Purnama, Indah Dian; Makmun, Armanto; Wijaya, Fanny (Journal La Medihealtico, 2024)
Hypertension is abnormally high blood pressure, measured on at least three different occasions. Hypertension is considered if systolic blood pressure is ≥140 mmHg and diastolic blood pressure is ≥90 mmHg. Currently, hypertension has become a global problem because its prevalence continues to increase from year to year. This disease can trigger other diseases such as stroke, coronary heart disease, heart failure, and kidney disease. Obesity also has a close relationship with the occurrence of hypertension. The greater the body mass, the more blood is needed to supply oxygen and food to body tissues. In addition to pharmacological therapy, one alternative treatment that can be an option to lower blood pressure is to consume herbal plants. One of the herbal plants that can lower blood pressure is soursop leaf decoction. Patients with complaints of headaches, weakness, tension in the back of the neck, accompanied by a history of hypertension and obesity, with a diagnosis of Hypertension and Obesity are given therapy in the form of Paracetamol 500 mg 3x1 and Amlodipine 10 mg 1x1. Pharmacological interventions produced good results, namely controlled blood pressure in patients. The hypertension suffered by the patient is hypertension that is obtained due to several predisposing factors in the patient, namely age, gender, smoking habits, and obesity.